Pengaruh Pemberian Pupuk Bokasi Rumput Naga (Potamogeton Sp.) Terhadap Pertumbuhan Dan Hasil Tanaman Sawi (Brassica Juncea L.) - Imbran, Rusydy; Khamidah, Noor; Rizali, Akhmad (Universitas Lambung Mangkurat, 2024)
Organic fertilizers can be in solid or liquid form, most organic fertilizers are in solid form such as manure and compost. The dragon grass (Potamogeton Sp) is one of the organic components that can be used to make bokashi fertilizer.This plant is a plant that lives in water, has a creeping rhizome and leafy branches, the leaf blades can float or submerge, and the stems are often joined. This plant does not have stomata on the leaves. The genus is generally divided into two groups, namely broadleaf and linear leaf. According to the results of the Balitra content test (2019), the dragon grass plant contains N = 3.36%, P = 0.41, K = 3.10. The purpose of this study is to see how providing dragon grass bokashi (Potamogeton sp) affects mustard greens development and yield (Brassica juncea L.). The study took place at the Banjarbaru agro-ecotechnology experimental garden(hortibun), Banjarbaru, South Kalimantan from January until March 2021. This research utilised a factorial Randomized Block Design (RAK) with two factors: K0: without giving bokashi fertilizer (Control); K1: 10 tons/ha equals 19.37 g (Bokashi Dragon Grass); K2: 15 Tons/ha = 29.06 g Bokashi Dragon Grass; K3: 20 Tons/ha = 38.75 g Bokashi Dragon Grass; K4: 25 Tons/ha = 48.44 g Bokashi Dragon Grass (Bokashi Dragon Grass).To produce 20 experimental units, each experiment was repeated 4 times.